Co-evolution of Enzymes Involved in Plant Cell Wall Metabolism in the Grasses - Bulone, Vincent; Schwerdt, Julian G.; Fincher, Geoffrey B. (Frontiers in Plant Science, 2019)
There has been a dramatic evolutionary shift in the polysaccharide composition of cell walls in the grasses, with increases in arabinoxylans and (1,3;1,4)-β-glucans and decreases in pectic polysaccharides, mannans, and xyloglucans, compared with other angiosperms. Several enzymes are involved in the biosynthesis of arabinoxylans, but the overall process is not yet defined and whether their increased abundance in grasses results from active or reactive evolutionary forces is not clear. Phylogenetic analyses reveal that multiple independent evolution of genes encoding (1,3;1,4)-β-glucan synthases has probably occurred within the large cellulose synthase/cellulose synthase-like (CesA/Csl) gene family of angiosperms. The (1,3;1,4)-β-glucan synthases appear to be capable of inserting both (1,3)- and (1,4)-β-linkages in the elongating polysaccharide chain, although the precise mechanism through which this is achieved remains unclear. Nevertheless, these enzymes probably evolved from synthases that originally synthesized only (1,4)-β-linkages. Initially, (1,3;1,4)-β-glucans could be turned over through preexisting cellulases, but as the need for specific hydrolysis was required, the grasses evolved specific (1,3;1,4)-β-glucan endohydrolases. The corresponding genes evolved from genes for the more widely distributed (1,3)-β-glucan endohydrolases. Why the subgroups of CesA/Csl genes that mediate the synthesis of (1,3;1,4)-β-glucans have been retained by the highly successful grasses but by few other angiosperms or lower plants represents an intriguing biological question. In this review, we address this important aspect of cell wall polysaccharide evolution in the grasses, with a particular focus on the enzymes involved in noncellulosic polysaccharide biosynthesis, hydrolysis, and modification.